Academic administration strategies of school administrators under the Office of the Secondary Education Service Area, Phetchaburi. - Samli, Surin; Seangsuwan , Tawat; Mongkolsith, Suda (Journal of MCU Phetchaburi Review, 2025)
Abstract This research aimed to study the academic administration strategies of school administrators under the Office of the Secondary Education Service Area, Phetchaburi in 4 aspects: 1) environmental inspection, strategic planning, strategy implementation, and strategy control and evaluation. The four academic administration strategies were compared, classified by school size, and the academic administration strategies were analyzed. The sample consisted of 285 teachers, who were selected using the Krejci and Morgan table using the stratified random sampling method. The qualified persons for interviews were 5 school administrators under the Office of the Secondary Education Service Area, Phetchaburi, using the purposive sampling method. The instruments used for data collection were questionnaires with a reliability of 0.347 and interview forms. Data analysis from the questionnaires used statistics such as frequency, percentage, standard deviation, F-test, and Scheffe’s method. Content analysis was used for the interviews. The results of the research found that 1) the academic administration strategies of school administrators according to teachers’ opinions were at a moderate level overall. When considering each aspect, strategic planning was at a high level, and environmental inspection The strategy implementation and strategy control and evaluation aspects were at a moderate level. 2) A comparison of teachers’ opinions on academic administration strategies of school administrators under the Office of the Secondary Education Service Area, Phetchaburi, found that they were statistically significantly different at the .05 level. Teachers working in different sized schools had significantly different opinions on academic administration strategies of school administrators at the .05 level. 3) The results of the analysis of academic administration strategies of school administrators under the Office of the Secondary Education Service Area, Phetchaburi, consisted of vision, mission, objectives, and 3 levels of 11 strategies.